2023
DOI: 10.1038/s41598-023-46632-9
|View full text |Cite
|
Sign up to set email alerts
|

Global and local drivers of Echinococcus multilocularis infection in the western Balkan region

Sibusiso Moloi,
Tamás Tari,
Tibor Halász
et al.

Abstract: The cestode, Echinococcus multilocularis, is one of the most threatening parasitic challenges in the European Union. Despite the warming climate, the parasite intensively spread in Europe's colder and warmer regions. Little is known about the expansion of E. multilocularis in the Balkan region. Ordinary least squares, geographically weighted and multi-scale geographically weighted regressions were used to detect global and local drivers that influenced the prevalence in red foxes and golden jackals in the sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The variation in selective effect of different types of hosts causes oscillation in the gene frequency, thus relative breeding success of different generations [14,43]. Previous studies in the same carnivore communities suggested that golden jackal might generate a higher risk for HAE than red fox [11,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variation in selective effect of different types of hosts causes oscillation in the gene frequency, thus relative breeding success of different generations [14,43]. Previous studies in the same carnivore communities suggested that golden jackal might generate a higher risk for HAE than red fox [11,44].…”
Section: Discussionmentioning
confidence: 99%
“…The research is based on worms collected from red fox and golden jackal specimens investigated in previous studies [11,44]. All specimens originated from carcasses, which were harvested by legal hunt in the framework of authorised wildlife management plans.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation